Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/jcb.21071
|View full text |Cite
|
Sign up to set email alerts
|

Increase in β1‐6 GlcNAc branching caused by N‐acetylglucosaminyltransferase V directs integrin β1 stability in human hepatocellular carcinoma cell line SMMC‐7721

Abstract: In this study, an enzymatic inactive mutant of GnT-V (DcGnT-V) was constructed and transfected in SMMC 7721 cell line. Integrin b1 in DcGnT-V transfectants (Dc-7721) showed attenuation of the number of b1-6 GlcNAc branching, whereas those in wtGnT-V transfectants (wt-7721) presented a b1-6 GlcNAc-rich pattern. High integrin b1 expression was observed in wt-7721 compared with mock cells (7721 cell transfected with the vector pcDNA3), while transfection of DcGnT-V decreased the integrin b1 expression, despite of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…Furthermore, depletion of the Mgat5-modified glycans by swainsonine can enhance Ag-dependent T cell proliferation in vitro (16), and similar results were observed in Mgat5 gene knockout mice (13). Recently it was reported that Mgat5 directed integrin stability (17) and regulated expression of cytokine receptors, which balances their surface retention against loss via endocytosis (18). These reports suggest that stimulated IFN-␥ production and enhanced T cell activation and differentiation might be achieved by down-regulation of Mgat5.…”
mentioning
confidence: 70%
“…Furthermore, depletion of the Mgat5-modified glycans by swainsonine can enhance Ag-dependent T cell proliferation in vitro (16), and similar results were observed in Mgat5 gene knockout mice (13). Recently it was reported that Mgat5 directed integrin stability (17) and regulated expression of cytokine receptors, which balances their surface retention against loss via endocytosis (18). These reports suggest that stimulated IFN-␥ production and enhanced T cell activation and differentiation might be achieved by down-regulation of Mgat5.…”
mentioning
confidence: 70%
“…S6B). The mature form of ITGB1 showed the same reduction, but persisted longer that the newly synthesized form, apparently because of the fact that it is glycosylated and, thus, more stable than the nascent ITGB1 polypeptide (25). After 9 h of incubation with 10 g/ml cycloheximide (a lower concentration of the drug was necessary to avoid cell death), the mature ITGB1 (upper band) started diminishing as well.…”
Section: Expression Of Mrad9 Restores Migration and Invasion Potentiamentioning
confidence: 91%
“…The protein A/G plus-agarose was purchased from Santa Cruz (Santa Cruz, CA, USA). The production of horseradish peroxidaselinked lectins Galanthus nivalis agglutinin (GNA) and wheat germ agglutinin (WGA) were performed as described previously [39].…”
Section: Cell Lines Antibodies and Reagentsmentioning
confidence: 99%